REDE DE APOIO AOS ESTUDANTES: SEU PAPEL NO PROCESSO DE APRENDIZAGEM DOS ESTUDANTES NO INSTITUTO FEDERAL FARROUPILHA – CAMPUS SÃO VICENTE DO SUL - Lorenzoni, Janete Cordeiro (2019)
The dissertation aimed to investigate the extent to which the work of the Student Support Network contributes to the learning process of this public at the Federal Institute Farroupilha - São Vicente do Sul Campus (IFFAR). Specifically, it was intended to identify the professional profile of the servers that make up thenetwork, to map the actions and strategies carried out by the professionals, to point out the results of these actions and strategies, as well as to reflect on their potentialities and weaknesses, and to propose new actions and strategies to the network. As for the methodology, the qualitative approach was used for bibliographic review, documentary research and field research. As a methodological strategy, the case study, as a technique, the semi-structured interview was chosen and content analysis was chosen to analyze the results. Field research was carried out by sampling among the professionals of the mentioned campus that are part of the network, and the data collection was done in 2017, through semi-structured interviews. In documentary research IFFAR institutional documents were used. The development of the interviews took place in the work place of the professionals, guided by a script of questions elaborated according to the theme of the research: The role of the Student Support Network in the learning processes at the Federal Institute Farroupilha - São Vicente do Sul Campus. Subsequently, the data were analyzed and five thematic categories were constructed: 1) students’ demands; 2) Networking; 3) professionals’ actions and strategies; 4) results and contributions to the learning process; 5) Network shortcomings. Based on these analyzes, it was realized that the professionals understood that, given the complexity of the demands, the integrated work that provides the exchange of knowledge and knowledge achieves greater effectiveness in the mediation or resolution of situations and, thus, contributes to the process of student learning. That the actions and strategies used for attendance and/or referrals are organized according to the complexity of each demand, and can be performed individually by a professional or in network, with more professionals, in an interdisciplinary way. In addition to the work done with the students and their contribution to the learning process, concerns were also expressed about the permanent qualification of this service, considering the complexity of the demands that are presented in the daily school life, pointing out how necessary the maintenance of a permanent space for dialogue between professionals, both for the organization of joint work, and for the formation and strengthening of bonds and bonds of solidarity and professional support. It was evidenced that there is also the need to implement the organization of data and information on the demands served or in attendance, in order to dynamize and qualify the actions with the students. Therefore, it is believed that given the size of the campus, its quantitative of students and their needs, the work of the Network is relevant to students, reflecting in a positive way the people of their conviviality and the school environment, strengthening themselves with the possibility of developing actions in an integrated way with the other professionals through exchange of knowledge, providing the understanding of the demands in their complexity and, consequently, the development of effective actions with the students, contributing to their student life.